2012
DOI: 10.1136/acupmed-2012-010127
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Acupuncture on Leptin, Ghrelin, Insulin and Cholecystokinin in Obese Women: A Randomised, Sham-Controlled Preliminary Trial

Abstract: Background Obesity is an energy balance problem caused by overeating. Obesity treatment includes diet, exercise, behaviour treatment, pharmacotherapy and surgery; in addition, acupuncture is also an option. Objective To investigate the effect of acupuncture on weight loss and whether a brief acupuncture treatment of 5 weeks can change circulating levels of leptin, ghrelin, insulin and cholecystokinin (CCK) in obese women. Methods 40 women with a body mass index (BMI)>30 kg/m 2 were equally randomised to either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 26 publications
1
68
0
3
Order By: Relevance
“…This longitudinal study indicated this method is suitable and effective for the prevention of hyperlipidemia and neuropathy in patients with type 2 diabetes; results of the study also showed this intervention is suitable for the improvement of kidney functions in such patients (26). However, results of a study, showed that bilateral acupressure at LI-4, HT-7, ST-36, ST-44, and SP-6 points could reduce the level of insulin in females with obesity (20). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This longitudinal study indicated this method is suitable and effective for the prevention of hyperlipidemia and neuropathy in patients with type 2 diabetes; results of the study also showed this intervention is suitable for the improvement of kidney functions in such patients (26). However, results of a study, showed that bilateral acupressure at LI-4, HT-7, ST-36, ST-44, and SP-6 points could reduce the level of insulin in females with obesity (20). …”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 shows the acupressure points. The total time of acupressure was 20 minutes (5 minutes at each point) in 10 seconds of pressure - and 2 seconds of rest periods (20, 21). Intervention was carried out every day at 10:00 a.m. for 3 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Both manual 72 83 and auricular acupuncture 74 as well as EA 79 83 exert a beneficial effect on leptin resistance and cause a significant decrease in plasma leptin levels in obese patients compared with sham 72 74 or diet alone. 79 In addition, manual 72 and auricular 74 acupuncture significantly increase ghrelin levels in comparison with sham, while EA seems to cause a remarkable increase in β endorphin 79 and adiponectin 83 in parallel to weight loss.…”
Section: Effect Of Different Types Of Acupuncture On Body Weight Alonementioning
confidence: 94%
“…9 Although the mechanism by which acupuncture helps to reduce obesity is not clear, several studies suggest that it increases the neural activity associated with the ventromedial nuclei of the hypothalamus, raises the tone of the smooth muscle of the stomach and decreases circulating leptin and insulin levels. 10 Since nesfatin-1 is an anorexigenic protein newly associated with loss of appetite, we hypothesised that it might be involved in the effects of acupuncture on obesity. In this study, we compared plasma nesfatin-1 levels of obese patients and normal weight controls, investigated the relationship between nesfatin-1 level and anthropometric and metabolic parameters in obese patients and examined the change in plasma nesfatin-1 level after acupuncture treatment in obese patients.…”
Section: Introductionmentioning
confidence: 99%